Pendekatan Hermeneutika Ricoeur dalam Teologi Inklusif untuk Menanggapi Konflik Etnis dan Budaya di Masyarakat Multikultural - Stasha Diva Sudijanto; Rinawati Rinawati; Agus Suhariono (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Ethnic and cultural diversity in modern society has become increasingly complex due to the influences of globalization, urbanization, and migration, resulting in multicultural communities. This diversity, while offering opportunities for mutual understanding, often gives rise to tensions, prejudices, and even conflicts between groups, especially when cultural identities are contested. In such circumstances, religion plays a significant role as a social pillar that can embrace differences. However, if applied exclusively, religion also has the potential to become a source of conflict. Therefore, inclusive theology, which prioritizes acceptance of differences without compromising religious teachings, becomes a relevant solution to bridge these tensions. Inclusive theology not only encourages intercultural dialogue but also promotes peace and solidarity by emphasizing love, tolerance, and respect for the dignity of every individual. In the context of the church, inclusive theology serves as an agent of peace actively addressing issues of ethnic discrimination and cultural injustice. This study aims to explore the application of inclusive theology in responding to ethnic and cultural conflicts in multicultural societies, using a qualitative approach and Ricoeur's hermeneutic analysis. It is expected that this research will contribute to fostering harmony and reconciliation amidst existing diversity.